If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2 + -2c) = 28 (2 * 2 + -2c * 2) = 28 (4 + -4c) = 28 Solving 4 + -4c = 28 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -4c = 28 + -4 Combine like terms: 4 + -4 = 0 0 + -4c = 28 + -4 -4c = 28 + -4 Combine like terms: 28 + -4 = 24 -4c = 24 Divide each side by '-4'. c = -6 Simplifying c = -6
| -4.9x^2+2x+10=0 | | 12+6x=-4x^2 | | 8x-2+4x+14=180 | | 5z+9=2z-3 | | p/8+5=9 | | 8x-2=4x+14 | | 98-3x=24x+23 | | 4x-8=28-2x | | 500-25x=-250+50x | | 7-x+3x-3-8x= | | -5(x+4)=-6x | | s=2*2.14rh | | -3(7n-4)+4n= | | (3y+1)+25= | | 7.7(x-2)=-0.3x+40.6 | | -81=-9k | | 10x-5x=5 | | -8=a+3 | | -5(n-1)-4h= | | 1x^2-3x+2=0 | | -2(9p+5)= | | y=.75x+2 | | 6(d+1)= | | 6(2x+3)=-9 | | 3y-7+5y-9= | | -3(x-5)=3(x-1) | | -6(2+3)+52= | | 16y-22y= | | A=1/2*10(6+15) | | x^2=-5 | | x^2-25=2x | | 5(2+x)+2x=20-(2x+6) |